ANALISIS EFEKTIVITAS IKLAN DI INSTAGRAM DALAM MENINGKATKAN BRAND AWARENESS - Novita Nilla Fauzia; Qoni’ah Nur Wijayani (JOURNAL SAINS STUDENT RESEARCH, 2024)
Advertising is a message or information that is used to promote certain goods or services to an audience or public. Advertising is one way of marketing media and promoting a product and service aimed at potential consumers. The purpose of advertising by companies is to influence or persuade the general public to be interested in the products being promoted. One of the popular social media that has become a promotional tool for marketing and advertising products and services is Instagram. Currently, Instagram has launched an advertising feature known as Instagram ads. So, advertising can build Brand Awareness, increase sales, and convince consumers to use these products and services. Advertising is more focused and aimed at the effectiveness of advertising on Instagram in increasing Brand Awareness. This research uses qualitative methods, with data collection techniques through observation. Increasing brand awareness through advertising on Instagram has the aim of getting as much attention as possible from users of the platform with the aim of getting recognition for its existence with the many social interactions that occur during its implementation. The research results show that Instagram advertising has a positive and significant influence on brand awareness. The implication of this research is the importance of using advertising on Instagram as a marketing strategy to increase brand awareness.